Fort Marlborough Ethnomathematics-Based Learning Handouts: Enhancing High School Students' Mathematical Literacy Skills - Susanto, Edi; Aziza, Mela; Hiasa, Fina; Disha Stanggo, Pratiwi (FKIP Universitas Lampung, 2025)
This study aims to develop a valid, practical, and effective learning handout based on the ethnomathematics of Fort Marlborough, Bengkulu, to enhance students' mathematical literacy. The research method used is research and development. The development model used is a formative evaluation with stages including self-evaluation, expert review, face-to-face sessions, small-group sessions, and field testing. This study involved test subjects of grade X high school students in Bengkulu City, Indonesia. The test subjects in this study were divided into several stages of the research. This study involved four experts (mathematics lecturers) from different universities. The one-to-one test stage involved six high school students (high, medium, and low abilities). The limited-scale test stage involved 24 grade X high school students, and the large-scale implementation with 43 subjects. Data collection techniques used were observation, questionnaires, and tests. Data analysis was carried out quantitatively and qualitatively. Quantitative and qualitative analyses examined the validity, practicality, and effectiveness of the mathematical literacy test. Analysis was also carried out descriptively on the results of suggestions from expert assessments of research products. The results of the study showed that: 1) the trigonometry learning handout based on the ethnomathematics of Fort Malborough Bengkulu that was developed meets the valid criteria based on the assessment of material, construction, and language by experts, with an average score of 0.63 (valid). 2) The trigonometry learning handout meets the practical criteria based on student assessment, with an average response score of 3.43 (very practical). The trigonometry learning handout has the potential to enhance high school students' mathematical literacy skills. In developing teaching materials using context, it is necessary to choose the proper context, and the illustration must be clear and easy to understand, in accordance with the material. Keywords: learning handout, ethnomathematics, Fort Marlborough, mathematical literacy skills.